Mixed perceptions of women on care in maternal and child healthcare settings in Lilongwe, Malawi - Andrew Simwaka; Ezereth Kabuluzi; Berlington Munkhondya; Lucy Ngoma; Hlalapi Kunkeyani; Tiwonge Ethel Mbeya Munkhondya; Gladys Msiska (Elsevier, 2020)
Background: This paper reports findings of a study which was conducted in response to a plethora of negative patient/client experiences which occur in various clinical settings in Malawi and are commonly reported in the media. The study was aimed at embedding compassionate care in selected maternal and child healthcare settings where the study was conducted. Research methodology: The study employed a qualitative methodology which utilized an exploratory-descriptive qualitative design. However, this was part of a larger Participatory Action Research Study (PAR). In-depth exit interviews were conducted with women who were discharged from postnatal ward and women whose babies or children were discharged from nursery and paediatric ward respectively. The study had a sample of 30 participants who were purposively selected. Thematic analysis was conducted. Findings: The findings revealed the perceptions of women of the care rendered in the maternal and child health care settings where the study was conducted. The study revealed mixed perceptions of the women on the care. More commonly, the women perceived that the care was good. However, some women perceived that the care was poor. Three main themes emerged from the data and these include: women's perception of good care in maternal and child healthcare settings; women's perception of poor care in maternal and child healthcare settings and Perceptions of women on personnel and healthcare facility factors essential for improved care. Conclusion: The study revealed positive caring encounters and this implies that nurses and midwives in Malawi can still care. It is therefore argued that caring is not completely a lost virtue. Mentorship through a compassionate leadership strategy is proposed to enhance the delivery of compassionate care.